2018
DOI: 10.31294/w.v10i2.3862
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguity in Soundtrack Songs Lyric of Moana Movie

Abstract: The objective of this study is to identify the ambiguity in soundtrack song lyrics of Moana Movie. This study used descriptive method to analyze data. The research data collected from "We Know The Way" lyrics and 'I'm Moana" by soundtrack songs lyric of Moana movie. The result of this study is indicated that : (1) There are 26 ambiguity, 8 structural ambiguity and 18 lexical ambiguity in "We Know the Way" lyric and in "I'm Moana" lyrics there are 45 ambiguity, consist of 10 structural ambiguity and 35 lexical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The results of the analysis indicate that from four advertisements, one is caused by homonymy (plate 4: Advertisement of Facebook); two of the others are caused by puns and homonymy (plate 1& 2: Advertisements of Big Cola and McDonald); and the last is caused by metaphor (plate 3: Advertisement of Toyota PRIUS). The last article is from Yastanti & Setiawati (2018), they have had analyzed the ambiguity in the soundtrack lyrics of the Moana movie. The result showed that in "We Know the Way" lyric, there are 26 ambiguity consist of 8 structural ambiguity and 18 lexical ambiguity; and there are 45 ambiguity, consist of 10 structural ambiguity and 35 lexical ambiguity in "I"m Moana" lyric.…”
Section: Romadlanimentioning
confidence: 99%
“…The results of the analysis indicate that from four advertisements, one is caused by homonymy (plate 4: Advertisement of Facebook); two of the others are caused by puns and homonymy (plate 1& 2: Advertisements of Big Cola and McDonald); and the last is caused by metaphor (plate 3: Advertisement of Toyota PRIUS). The last article is from Yastanti & Setiawati (2018), they have had analyzed the ambiguity in the soundtrack lyrics of the Moana movie. The result showed that in "We Know the Way" lyric, there are 26 ambiguity consist of 8 structural ambiguity and 18 lexical ambiguity; and there are 45 ambiguity, consist of 10 structural ambiguity and 35 lexical ambiguity in "I"m Moana" lyric.…”
Section: Romadlanimentioning
confidence: 99%
“…By analyzing Scott's song's semantic meaning, the writer aims to showcase the possibilities of meaning and the purposeful role of linguistics in English as a language used by the general population. Song lyrics is one of the creations has a deep meaning that try to deliver for the listener (Yastanti and Setiawati, 2018). This research will be focusing on the linguistics aspects of the song You Are the Reason, as performed by Calum Scott and will highlight the semantic meaning behind the lyrics of the song.…”
Section: Introductionmentioning
confidence: 99%
“…Movie may contain inspiration, knowledge, and someone's experience. Movie was made to entertain those viewers, give them a moral message, and also motivation (Yastanti & Widhiyanto, 2018;Arfani, 2018;Santas, 2002;Petrie & Boggs, 2008).…”
Section: Introductionmentioning
confidence: 99%